Disinformation on TikTok: Analyzing Hoaxes Surrounding the 2024 Indonesian Election - Wulandari, Charisma Dina; Munadhil Abdul; Tayibnapis, Radita Gora; Muzykant, Valerii Leodonovic (EKSPRESI DAN PERSEPSI : JURNAL ILMU KOMUNIKASI, 2025)
This research investigates the dissemination of hoax content related to the 2024 Indonesian General Election (#Pemilu2024) on TikTok, highlighting the platform's role in the spread of disinformation. A mixed-methods approach was employed, combining a literature review with primary data collected from TikTok via web scraping and secondary data sourced from Turnbackhoaks.id and media reports. Content and message analysis, along with Naïve Bayes classification, were employed to investigate the types of hoaxes, their dissemination patterns, and audience responses. Data triangulation ensured validity and reliability. Findings revealed a concerning prevalence of political hoaxes, including black campaigns and attempts to manipulate public opinion, rapidly spread by TikTok's short-form video format. The Naïve Bayes method classified comments on #Pemilu2024 TikTok videos with an accuracy rate of 87.37%. After preprocessing, 414 comments were analyzed, comprising 127 negative, 237 positive, and 50 neutral comments. The Naïve Bayes method effectively predicts sentiment in TikTok comments related to #Pemilu2024. The analysis reveals that social media videos can easily influence the Indonesian people without verifying information on official websites.